The Modern Theologians : an introduction to Christian theology since 1918 - Ford, David, 1948-; Muers, Rachel (The great theologians, 2005)
Provides a comprehensive overview of the main Christian theologies of the twentieth and twenty-first centuries. Each chapter in this book, is written by a leading theologian and gives a picture of a particular movement, topic or individual. Together these provide a picture of the development of modern theology.